PERAN MEDIA WHATSAPP GROUP PADA PERILAKU INFORMASI PADA IBU RUMAH TANGGA DALAM MENERIMA INFORMASI DAKWAH - Maulida , Siti Salwa; Muslikhah , Febri Palupi; Yusnita , Titien (JURNAL SAHID DA'WATII, 2023)
This research aims to discuss the effectiveness of WhatsApp Group-based da'wah information in village communities. This research departs from the phenomenon of housewives searching for information on da'wah using Whatsapp Group (WAG) which occurred in Cibening 01 Village, Pamijahan District, Bogor Regency, West Java Province. This research uses descriptive-qualitative research using a field research approach. The results and discussion of this research show that housewives' search for information on da'wah based on WhatsApp Groups (WAG) is quite effective. From this research it can be seen that the information behavior of housewives regarding da'wah information both in past and present situations chooses based on the need for knowledge obtained, the cognitive gap in housewives chooses the most easily accessible, on the bridge of cognition housewives are able to use the internet , attend the recitation of the majlis taklim, and read books to find information, and for the results of the da'wah information obtained by housewives, they can apply it in their daily lives and practice it again with other people.